THE RELIABILITY AND ACCURACY OF INTERNATIONAL TRIAGE SCALE IN THE EMERGENCY DEPARTMENT (ED): A LITERATURE REVIEW - Parinding, Yunus (Jurnal Ilmiah Kesehatan Promotif, 2024)
A large number of patient visits to the Emergency Department (ED) will influence the outcome of the services provided. The triage scale is one method designed to manage patient screening for quality service improvement. Several triage scales are employed internationally in the EDs including the Australasian Triage Scale (ATS), the Manchester Triage System (MTS), the Canadian Triage and Accuracy Scale (CTAS), and the Emergency Severity Index (ESI). Several studies have a concern to identify the reliability of the triage scale, but only a few of them identified the accuracy of the triage scale. The purpose of this literature review was to identify the best reliability and accuracy among ATS, MTS, CTAS, and ESI based on the literature. The literature search was conducted on electronic databases EBSCO and PubMed with keywords including (triage OR emergency department triage) AND reliability AND ((the Canadian Triage and Accuracy Scale OR CTAS) AND (the Australasian Triage Scale OR ATS) AND (the Manchester Triage System OR MTS) AND the Emergency Severity Index OR ESI)). Assessment of articles was composed based on the PRISMA format with criteria including primary research articles containing the reliability and accuracy of the triage scale in English and published between 2009 – 2019. A total of 271 publications were identified and only 10 studies were included in this literature review. The results reveal that ATS has a moderate level of reliability (k = 04 – 0.57) with an accuracy of 46.2% – 58.3%, CTAS has a good level reliability (k = 0.770) with accuracy of 49%, MTS have good to excellent level of reliability (k = 0.61 – 0.95) with accuracy of 49%, and ESI have moderate to excellent level reliability (k = 0.45 – 0.94) with accuracy of 59.6 % – 72.5%. Based on this review, MTS and ESI are the triage scale with the highest reliability and accuracy. Therefore, MTS and ESI are highly recommended in the ED. However, each EDs need to pay attention to the characteristics, culture, and available resources before choosing and implementing an appropriate triage scale